Untraditional caring arrangements among parents living apart. The case of Norway - Ragni Hege Kitterød; Jan Lyngstad (Statistics Norway, Research Department, 2011)
In spite of more symmetric parental roles in couples, shared residence is still practiced by a minority of parents following partnership dissolution in Norway, and the same is true for father sole custody. Utilising a survey of parents living apart in 2004, we find that shared residence is particularly likely when the father has a medium or high income, the mother is highly educated, the parents split up rather recently, the mother is currently married and the parents have no other children in their present households. Father sole custody is most likely when the mother has low income, the father has high income, the parents were formally married prior to the breakup, the child is a boy, the child is fairly old, the father is single and the mother has children in her current household. More equal parenting roles in couples in younger generations as well as policies urging parents to collaborate about their children's upbringing when they split up, may lead to an increase in shared residence in the years to come, and perhaps also to new groups of parents practicing such an arrangement.
Keywords: J12; J13; 330; Father sole custody; gender equality; parents living apart; shared residence.